Sustainability decision-making in small-to-medium enterprises: A study of SME managers' experience of sustainability tensions - Andrew, Sean Khaya (Research of GSB, 2017)
Due to competing strategic demands and limited resources, small-to-medium sized enterprise (SME) managers struggle to integrate sustainability comprehensively into their firms' strategy, while increasingly being targeted as significant contributors of unsustainable practices that compromise environmental services and societal wellbeing. Studies on why managers struggle to integrate sustainability strategies into their firms suggest managers face interrelated yet competing demands that surface a diversity of sustainability tensions that go beyond the traditional triad of economic, social and environmental agendas. The literature has primarily focused on the conscious cognitive sensemaking processes of managers in larger corporations as they face sustainability tensions. This lens does not surface the range of other inner experiences like emotions, values, and intuition that influence individuals' sensemaking process. The resulting research question for this study asks how SME managers' experience of strategic sustainability tensions influences their sustainability decision-making process. This research aimed to surface the full range of conscious and unconscious inner experiences managers had during their sustainability sensemaking processes. SMEs were a favourable research context in which to delve into the significance of managers' internal experiences because managers have a high degree of decision-making control in their firms, and there is scarce empirical evidence on what leads SME managers to make sustainability decisions. Over a one-year period in an inductive qualitative and exploratory research process, I interviewed twelve SME managers from the Western Cape's metals and manufacturing sector twice through two rounds of interviews. This study finds that SME managers undergo a range of emotions that influence their sustainability sensemaking experience. Conflicting emotional sustainability triggers cause unconscious internal sustainability tensions for managers between their personal values and managerial responsibilities. The SME resource-constrained context causes managers to instinctually prioritise managerial responsibilities to keep their firm afloat and maintain their pride through the legacy of the company. This study contributes to the literature by unearthing and legitimising the range of experiences and tensions that influence SME managers' sustainability sensemaking processes. It prompts further examination into managers' experience of sustainability tensions in the SME context and what experiences lead to integrative sustainability decisionmaking in highly volatile SME environments.